Hermitian symmetric spaces and Kahler rigidity - Burger, Marc; Iozzi, Alessandra; Wienhard, Anna (Transformation groups, 2007)
We characterize irreducible Hermitian symmetric spaces which are not of tube type, both in terms of the topology of the space of triples of pairwise transverse points in the Shilov boundary, and of two invariants which we introduce, the Hermitian triple product and its complexification.